3D Acoustic Field Intensity Probe Design and Measurements - KOTUS, Józef; CZYŻEWSKI, Andrzej; KOSTEK, Bożena (Archives of Acoustics, 2016)
The aim of this paper is two-fold. First, some basic notions on acoustic field intensity and its measurement are shortly recalled. Then, the equipment and the measurement procedure used in the sound intensity in the performed research study are described. The second goal is to present details of the design of the engineered 3D intensity probe, as well as the algorithms developed and applied for that purpose. Results of the intensity probe measurements along with the calibration procedure are then contained and discussed. Comparison between the engineered and the reference commercial probe confirms that the designed construction is applicable to the sound field intensity measurements with a sufficient effectiveness.